2009
DOI: 10.1016/j.ejcts.2008.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of intraoperative pleural lavage cytology for lung cancer without carcinomatous pleuritis: importance in patients with early stage disease during long-term follow-up☆

Abstract: Based on the present analysis of long-term follow-up after operation, PLC may also be an independent prognostic factor. In particular, the PLC status of patients with stage I disease or adenocarcinoma type has an important impact on survival. PLC-positive findings may be a high risk for postoperative pleural recurrence. For PLC-positive patients with stage I disease, careful serial follow-up for more than 5 years is required while paying attention to late pleural recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In multivariate analyses, 18 studies [20], [31], [37], [39], [41], [42], [47], [49], [51], [53], [55], [57], [58], [61], [64][67] were significant compared with 13 studies [19], [21], [27], [29], [34], [40], [44], [46], [48], [54], [63], [68], [69] with non-significant results. Of these included significant or non- significant studies, 3 have duplicated survival data [29], [37], [70] and one has uncompleted data [53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In multivariate analyses, 18 studies [20], [31], [37], [39], [41], [42], [47], [49], [51], [53], [55], [57], [58], [61], [64][67] were significant compared with 13 studies [19], [21], [27], [29], [34], [40], [44], [46], [48], [54], [63], [68], [69] with non-significant results. Of these included significant or non- significant studies, 3 have duplicated survival data [29], [37], [70] and one has uncompleted data [53].…”
Section: Resultsmentioning
confidence: 99%
“…We next analyze the association between LVI and OS in NSCLC patients by univariate (28 studies, comprising 9,703 cases) [25], [27], [31], [33], [34], [39][52], [54][60], [62], [63] or multivariate analysis (25 studies, comprising 9,423 cases) [27], [31], [34], [39][42], [44], [46][49], [51], [54], [57], [58], [61], [63][69]. The pooled HR estimate was 1.97 (95% CI: 1.75–2.21; P <0.0001) by univariate analysis with a significant heterogeneity (Q = 62.17; I 2  = 51.7%, P <0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported survival data for patients with stage I only 3 9 12 24–27 31 32. Analysis suggested that the association between positive pre-resection PLC and a poor survival outcome was even more pronounced in this group.…”
Section: Resultsmentioning
confidence: 99%
“…11 In addition, another of our previous reports showed that the survival and disease-free rates of patients after a lobectomy for adenocarcinomas sized 16-20 mm and containing less than 50% GGO were significantly worse than for patients who underwent wedge resection for GGO-predominant adenocarcinomas. 12 Cases with mucinous lesions were not included in the present study, because the smear sample from them contains mainly mucus and histiocytes, rarely tumor cells. In addition, a mucinous adenocarcinoma can easily spread in an aerogenous manner.…”
Section: Discussionmentioning
confidence: 99%